The Correlation of Different Intensities Exercise on Telomere Length - Ananta, Chaya Ducinta; Cindy, Christie; Sulaeman, Try Christian; Hutabarat, Naomi; Kanggriani, Prisca Angelina; Juhanna, Indira Vidiari; Adiatmika, I Putu Gede (Sport and Fitness Journal; Vol 10 No 3 (2022): Volume 10, No.3, September 2022, 2022)
Many studies have been conducted to establish the connection between exercise and telomere length, but still have varying results. Telomeres are reiterative DNA sequences (5'-TTAGGGn-3') which function to protect genomic DNA from enzymatic degradation. Telomere length can be used as a biomarker of aging because its repetitive structures are known to be highly relevant in the cellular aging process and the shortening of telomeres that occurs with increasing age is considered as an important contributor to aging in organisms. Several factors that affect telomere length are oxidative stress, chronic inflammation, BMI, lifestyle such as smoking, alcohol intake, stress, increased insulin resistance, and exercise. This study aims to determine the correlation of exercise at different intensities on telomere length. The method used in this study is internet search for journals and articles through several websites. The eligible criteria include studies in English language published between 2012 and 2022. The studies that report the correlation of different intensities exercise on telomere length were selected for the systematic literature review. As a result, the people who perform moderate to vigorous physical activity more in their leisure time, have longer leukocyte telomere length (LTL) and long-term resistance training may exert a protective effect on muscle telomere length in the elderly. Several studies have reported a correlation between prevention of leukocyte telomere length shortening and exercise at a certain intensity successfully.